Opposite hemispheric asymmetries during the ionospheric storm of 29-31 August 2004 - Astafyeva, Elvira (2014)
By making use of multiple ground‐based and spaceborne instruments, we study ionospheric and thermospheric behavior during the moderately intense geomagnetic storm of 29–31 August 2004 (minimum Dst excursion of −128 nT). Although this storm was far from the strongest in solar cycle 23, it provoked quite interesting effects in the ionosphere, such as opposite hemispheric asymmetries in the ionospheric F layer and in the topside ionosphere and a development of the ionospheric superfountain effect in the postsunset sector. Data from ground‐based GPS receivers and ionosondes revealed large increase in total electron content (TEC) and in NmF2 in the southern hemisphere, whereas in the northern hemisphere, very weak or no effect was observed. On the contrary, the topside measurements indicated the occurrence of a positive storm in the northern hemisphere. Overall, the strongest storm time disturbances were observed in the postsunset sector (~20:30–21:30 LT), where satellite radar altimeters TOPEX and Jason 1, along with the CHAMP satellite showed ~250–400% TEC increase in the middle‐ and low‐latitude regions. The signatures of the ionospheric plasma enhancement were seen up to the height of the Defense Meteorological Satellite Program (DMSP) satellites (~840 km). As for the thermospheric storm, data of the Gravity Recovery and Climate Experiment (GRACE) satellite mission revealed no asymmetry in neutral density data in the evening sector (~17 UT); however, very strong hemispheric asymmetry was observed in the postsunset sector by CHAMP (~21 UT). Overall, neutral density increase in the postsunset sector was found to be much stronger than in the evening sector.